Evaluation of hydration with lactoferrin on late-instar Tenebrio molitor larvae performance and functional properties of obtained meal - Irene Ferri; Matteo Dell’Anno; Benedetta Canala; Stefano Magnaghi; Beatrice Petrali; Luciana Rossi (Italian Journal of Animal Science)
Insects represent a promising alternative protein source as food and feed. This study evaluated the use of lactoferrin as a hydration source in Tenebrio molitor larvae rearing, on animal performance, nutritional and functional characteristics of insect meals. Seven-week-old larvae were reared for 14 days and randomly divided into two experimental groups: control group (CTRL, n = 8) reared on wheat bran; treatment group (TRT, n = 8) reared on wheat bran and supplemented with lactoferrin solution as a hydration source at days 0, 4, 8, 12. Larvae weight and feed consumption were recorded weekly to calculate growth performance. At the end of the trial, larvae were collected for meal production, whose main nutritional characteristics and colour were analysed as well as antibacterial activity against O138 Escherichia coli. The results showed a lower larval mortality in the TRT group compared to the CTRL (p < 0.05). The nutritional composition of the insect meals revealed higher content of proteins (p < 0.05) in the TRT group. After 3 h (p < 0.05), the meals hydrated with lactoferrin demonstrated a higher E. coli inhibitory activity compared to the CTRL group. In conclusion, the functionality of insect meals was enhanced by using innovative ingredients as hydration sources capable of transferring bioactive properties.